2014
DOI: 10.5535/arm.2014.38.2.153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Neuromuscular Electrical Stimulation Therapy in Acute/Subacute Ischemic Stroke Patients With Dysphagia

Abstract: ObjectiveTo compare the outcome of an early application of neuromuscular electrical stimulation (NMES) combined with traditional dysphagia therapy (TDT) versus traditional dysphagia therapy only in acute/subacute ischemic stroke patients with moderate to severe dysphagia by videofluoroscopic swallowing study (VFSS).MethodsFifty-seven dysphagic stroke patients were enrolled in a VFSS within 10 days after stroke onset. Patients were randomly assigned into two treatment groups. Thirty-one patients received NMES c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 24 publications
3
50
0
2
Order By: Relevance
“…() found sustained benefit at 24 months post‐treatment (in a ‘preliminary case series’) and Lee et al . () at 12 weeks post‐treatment. We would therefore prioritize data collection on long‐term effects in a full‐scale study in order to clarify this issue in a larger group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() found sustained benefit at 24 months post‐treatment (in a ‘preliminary case series’) and Lee et al . () at 12 weeks post‐treatment. We would therefore prioritize data collection on long‐term effects in a full‐scale study in order to clarify this issue in a larger group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the four studies that did look at long-term follow-up, two found no long-term effect at 12 weeks (Terre andMearin 2015, Guillen-Sola et al 2017) and two found a lasting effect: Sun et al (2013) found sustained benefit at 24 months post-treatment (in a 'preliminary case series') and Lee et al (2014) at 12 weeks post-treatment. We would therefore prioritize data collection on longterm effects in a full-scale study in order to clarify this issue in a larger group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…One investigated neuromuscular electrical stimulation (NMES) of the infrahyoid region for patients within 10 days of supratentorial stroke with dysphagia, and found benefit of NMES over SC on the Functional Oral Intake Scale (FOIS) at 3, 6, and 12 weeks, as well as in the likelihood and speed of resuming oral feeding [80]. Limitations of the trial include small sample size and high rates of spontaneous recovery.…”
Section: Human Trialsmentioning
confidence: 99%
“…Coefficient of variation (CV) and bland-Altman analysis were used to assess agreement. Results: 15 patients (n = 5 and n = 10) of mean (SD) age 62 (16) and 66 (9) years old (p = 0,511), mean (SD) BMI 25 (3,5) and 28 (6) kg m −2 (p = 0,352) and mean (SD) IGS2 53 (26) and 52 (17) (p = 0,606) were included. In group 1 mean CV for each muscle was less than 6% and Bland-Altman analysis showed excellent agreement between examinations.…”
Section: Fig 1 Comparisson Of Boussignac System (Bs) Alone Versus Wmentioning
confidence: 99%